On the peculiarities of seborrheic keratosis pigmentation - A. K. Alexandrova; V. A. Smolyannikova (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Seborrheic keratosis (SK) is a common benign epithelial skin tumor that exists in a variety of clinical op - tions. The color of the tumor varies from yellow to dark brown, which leads to diagnostic errors. There is аlittle data about pigmentation of the SK in the literature. There is no consensus on the content of melanocytes in the SK.Objective: to study the nature of the distribution of melanin in the SK and its relationship with the number of melanocytes.Materials and methods. An analysis of 130 histological preparations with a verified diagnosis of SK and immunohistochemistry (IHC) test with monoclonal antibodies to Melan A (clone A103 ready-to-use) have been performed. Material sampling was performed in 130 patients with SK at the age of 46-77. In 48.5 % of the material was taken from places that are easily exposed to sunlight, 51.5 % - from places that are often closed, less prone to exposure to UV-radiation.Results. As a result of histological examination, three types of pigmentation of the SK were identified, depending on the accumulation and location of pigment in the tumor. IHC test with monoclonal antibodies to Melan A in all cases of SK revealed a significant decrease in the content of melanocytes (0.7-5 %), compared with the unaffected epidermis (10.7-14.3 %) (р = 0.001). The greatest number of melanocytes (3-5 %) was recorded in SK, which were removed from places exposed to UV radiation.Conclusions. A significant decrease in the content of melanocytes (less than 3 % of tumor cells) in the most pigmented SK (p = 0.0003), the lack of activation of melanogenesis in the tumor under the influence of UV radiation indicates the accumulation of pigment due to its slow utilization, due to aging and a de - crease in metabolismtumor cells.